BINARY PATTERN GENERATION OF POETIC ORDER IN SANSKRIT POETICMETERS - Kumar, Meena; Warnekar, C. S.; Saxena, Saurabh (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2015)
The Pattern generation and Analysis is the technique of recognizing an object say, a target in combat space. The combat space T consists of targets of three typesi) Wanted Targets W ii) Rejected Targets R iii) Unknown Targets U So that T = W ? R? UThe description of object is called pattern.Charaterization of pattern class by common properties shared by all of its members is another basic concept used in design of an pattern recognisationsystem. Main objective of this approach is to determine common properties from finite set of samplespatterns and to examine a new pattern for a suitable switch. In signal processing , the role of input is vital to recognize objects. The input to the digital computer refers to any data or instructions enteredinto the memory. Data is a set of meaningful perceptual observations about an entity expressed innumerical ,alphabetical, graphical or mixed form. While Instructions refer to a set of action commands issued to CPU to tell a computer how to perform the tasks necessary to process data into information.Digital computer can accept the input via written/typed form through keyboard or the spoken/audioform through microphone. A great deal of work has been done in evaluating speech as a means of computer input. The present paper suggests the rhythmic syllable arrangements in various poeticmeters as a means of audio input, directly producing binary code. Such binary syllable arrangementhas been envisaged by Pingalacharya [1] . His Chhandas Shastra or science of poetic meters inSanskrit is a well known classical treatise on Prosody. It deals with the rhythmic syllablearrangements in various poetic meters. According to Chhandas Shastra [2] every pronounced letter iseither “Laghu” or Short [0] and “Guru” or Long[1] and each poetic meter is based on their fixedsequence[3]. Hence desired binary input sequence could be produced merely by utterance ofcorresponding syllables. Case studies of over 15 sets of such voice samples by male/ female/childcandidates were conducted and the resulting binary sequences are presented with correspondingaccuracies.